Towards a sustainable subjectivity: thinking the ecolo - Valle Álvarez, Jorge (Anales del Seminario de Historia de la Filosofía, 2024)
The ecological crisis is the “Great Test” that humanity must face throughout this century, but the solutions proposed so far by international economic and political circles are based on a green capitalism that does not question the philosophical premises that underpin modern rationalism and which are at the root of the current crisis: extreme anthropocentrism, the devaluation of Nature and the consequent dominance of human beings over the natural world. This article therefore proposes to extend the notion of sustainability to the field of philosophy, with the aim of illuminating a new sustainable subjectivity that revalues Nature and knows itself to be integrated and not radically separated from it. To this end, the aim is to think about the ecological crisis from the perspective of the philosophy of María Zambrano, who, faced with the excesses of rationalism and the predominance of an arrogant, dominant and destructive reason that isolates human beings and violates and instrumentalises the world, proposes a poetic reason that, on the contrary, is humble, pursues the union of human beings with the other and is based on the love of Nature.
Keywords: ecological crisis; María Zambrano; poetic reason; sustainable subjectivity